Jean-Luc Godard, Cinema Historian - Witt, Michael (Book collections on Project MUSE., 2013)
Originally released as a videographic experiment in film history, Jean-Luc Godard's Histoire(s) du cinema has been widely hailed as a landmark in how we think about and narrate cinema history, and in how history is taught through cinema. This book explores Godard's landmark work as both a specimen of an artist's vision and a philosophical statement on the history of film. The author contextualizes Godard's theories and approaches to historiography and provides a guide to the wide-ranging cinematic, aesthetic, and cultural forces that shaped Godard.